Delivering high reliability in maternity care: In situ simulation as a source of organisational resilience. (August 2019) - Macrae, Carl; Draycott, Tim
Highlights: Routine use of on-site or 'in situ' simulation can be a driver systemic safety. In situ simulation supports both adaptive change and stabilizing routinisation. In situ simulation creates symbolic disruptions that lead to material adaptation. In situ simulation allows work-as-imagined to be tested against work-as-done. In situ simulation can both enhance positive practices and address weaknesses. Abstract: The fields of resilience engineering and high reliability organising both seek to explain the key sources and characteristics of safety in organisations that operate under conditions of considerable complexity, variability and surprise. A key focus in both of these fields is explaining how organisations can use adaptive and flexible work processes to deliver safe and reliable services, and how organisations can draw on past events and new experiences to increase their capacity to handle disruptive and unexpected events. To explore these issues, this paper develops an analysis of the routine use of on-site or 'in situ' simulation of emergency events as part of a systematic approach to safety management in the healthcare setting of maternity care. This analysis identifies three core organising processes through which in situ simulation can act as a source of organisational safety: relational rehearsal, system structuring and practice elaboration. We use this analysis to examine the opportunities that exist to develop more integrated explanatory accounts of high reliability organising and resilience engineering, particularly exploring the tensions between organisational stability and change, proactive and reactive modes of organising, and organisational strength and weakness.